Familial leiomyoma: a case report - Gutha, Swetha; Sampath, Shalini (International Journal of Research in Dermatology, 2021)
Cutaneous leiomyomas are benign tumors that can be exquisitely painful. Comprise three distinct types such as piloleimyoma, angioleiomyoma, and genital leiomyoma. Piloleiomyomas, derived from arrector pili muscle, are solitary or multiple firm papulonodules located mostly on the extremities and trunk; genital leiomyomas, derived from dartoic, vulvar, or mammary smooth muscle, are solitary or papulonodules located on the scrotum, vulva, or nipple; and angioleiomyomas, include solid, cavernous, or venous subtypes, are derived from the tunica media of small arteries and veins and typically present on the extremities. Excisional biopsy is required for diagnosing all cutaneous leiomyomas Histology shows interlacing fibers of spindle cells with moderate amounts of eosinophilic cytoplasm and a blunt-ended, elongated nucleus with perinuclear halos. Surgical excision is curative for cutaneous leiomyomas, with other management options including medical or destructive therapy. A 36-year-old male patient presented with a 13 years history of painful, multiple lesions over the back. Based on the histopathological examination, imaging, and past medical records, a diagnosis of familial leiomyoma was made. His brother had similar disease. The patient was started on tab gabapentin 300mg at night. Patient advised for carbon dioxide laser excision. The present case report has been reported for its interesting clinical presentations and rarity.